Spatial patterns and clustering of dengue incidence in Mexico: Analysis of Moran’s index across 2,471 municipalities from 2022 to 2024 - Oliver Mendoza-Cano; Rogelio Danis-Lozano; Xóchitl Trujillo; Miguel Huerta; Mónica Ríos-Silva; Agustin Lugo-Radillo; Jaime Alberto Bricio-Barrios; Verónica Benites-Godínez; Herguin Benjamin Cuevas-Arellano; Juan Manuel Uribe-Ramos; Ramón Solano-Barajas; Yolitzy Cárdenas; et al. (PLoS ONE, 2025)
Dengue is an increasing public health challenge, with rising cases and expanding distribution. Its complex epidemiology is influenced by climate change, urbanization, and the circulation of multiple viral serotypes. This study aimed to characterize the spatial and temporal (2022–2024) patterns of dengue incidence across 2,471 municipalities in Mexico. Weekly case counts, obtained through the normative epidemiological surveillance system for vector-borne diseases, were used to calculate incidence rates per 100,000 population. Geographic Information Systems were employed to analyze spatial patterns, while Local Moran’s I statistic and a k-nearest neighbors spatial weights matrix identified spatial clusters. A total of 622,689 dengue cases were analyzed, with incidence rates rising from 29.4 in 2022 to 279.0 per 100,000 in 2024. Dengue transmission expanded, affecting 38.0% of municipalities in 2022 and 68.6% by 2024 (p < 0.001). Spatial clustering also increased, with positive clusters increasing from 28 municipalities in 2022–98 in both 2023 and 2024. Moran’s I values indicated a peak in spatial autocorrelation in 2023 (I = 0.57). While DENV-2 was the predominant serotype in 2022, DENV-3 became dominant in 2023 and 2024. Over time, high-incidence areas shifted from southern and central regions to the southeast and Pacific coast. These findings suggest the growing burden of dengue in Mexico, driven by rising incidence, expanding geographic distribution, and evolving spatial patterns. A coordinated public health response is needed to mitigate the impact of dengue and prevent its spread to newly affected areas.